Stress-related expression of the chloroplast EGY3 pseudoprotease and its possible impact on chloroplasts’ proteome composition - Adamiec, Małgorzata; Dobrogojski, Jędrzej; Wojtyla, Łukasz; Luciński, Robert (Frontiers in Plant Science, 2022)
The EGY3 is a pseudoprotease, located in thylakoid membrane, that shares homology with the family of site-2-proteases (S2P). Although S2P proteases are present in the cells of all living organisms the EGY3 was found only in plant cells. The sequence of the pseudoprotease is highly conserved in the plant kingdom, however, its function remains unknown. Results, obtained with real-time PCR indicated that the expression of the EGY3 gene is dramatically induced during the first few hours of exposition to high light and high-temperature stress. The observed increase in transcript abundance correlates with protein accumulation level, which indicates that EGY3 participates in response to both high temperature and high light stresses. The lack of the pseudoprotease leads, in both of these stresses to a decrease in abundance located in chloroplast copper/zinc superoxide dismutase 2 and lower concentrations of hydrogen peroxide. In both analyzed stressful conditions proteins related to RubisCO folding, glycine metabolism, and photosystem I were identified as differently accumulating in egy3 mutant lines and WT plants, however, the functional status of PSII during analyzed stressful conditions remains very similar. Our results lead to a conclusion that EGY3 pseudoprotease participates in response to high light and high-temperature stress, however, its role is associated rather with photosystem I and light-independent reactions of photosynthesis.